PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN MULSA HELAIAN ANAK DAUN KELAPA SAWIT PADA MEDIUM TANAM SUB SOIL BIBIT KELAPA SAWIT (Elaeisguineensis Jacq.) TAHAP MAIN NURSERY - Leonardo '; Arnis En Yulia; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of this research was to find out the effect of palm oil’s empty bunch fruit compost and palm oil’s leaflets mulch givingon sub soil oil palm seeds planting and determine the right dose of oil palm empty bunch fruit compost to support oil palm’s growth in main nurseryphase. This research was conducted from May 2015 until August 2014 located at the agricultural experimental station, University of Riau. The design that used in this research was Completely Randomized Design (CRD) consisted of 2 factors and 3 replications.The first factor was oil palm’s empty bunch fruit compost (K) consisted of 4 levels were : 0 g (K0), 50 g (K1), 75 g (K2) and 100 g/plant unit (K4).The second factor was palm oil’s leaflets mulch (M) consisted of 3 levels were : 0 g (M0), 50 g (M1) and 100 g/pant unit (M2). The result of this research showed that the combination of palm oil’s empty bunch fruit compost and palm oil’s leaflets mulch significantly affected on leaf area, but that is not significantly affected on plant height, leaf number and hump diameter on oil palm’s seed tenera Marihat variety growth on main nursery phase. Keywords:palm oil’s empty bunch fruit compost, palm oil’s leaflets mulch, main nursery